2016
DOI: 10.3892/mmr.2016.5938
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93 is overexpressed and induces apoptosis in glaucoma trabecular meshwork cells

Abstract: Glaucoma is an optic neuropathy and a major cause of blindness globally. Trabecular meshwork cells are important in maintaining aqueous humor flow, the dysfunction of which tends to induce glaucoma. As important regulators of gene expression, microRNAs may be crucial in regulating trabecular meshwork cells. The present study aimed to reveal the effect of microRNA‑93 (miR‑93) on glaucoma trabecular meshwork (GTM) cell apoptosis. The expression levels of miR‑93 were compared between human trabecular meshwork (HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…88 We also identified miR-93, which has been found to increase expression and induce apoptosis in glaucomatous TM cells. 89 Our integrative miRNA-mRNA expression analysis identified several miRNA-mRNA interactions in the TM cells, highlighting several miRNA master regulators, such as miR-125a-5p, miR-30a-3p, and miR-1275. Additional master miRNA regulators may be identified if we expand our analysis to include predicted targets with moderate confidence, although this would also potentially increase the number of false-positive findings.…”
Section: Mirna Regulation Of Stretch Responsive Genesmentioning
confidence: 87%
“…88 We also identified miR-93, which has been found to increase expression and induce apoptosis in glaucomatous TM cells. 89 Our integrative miRNA-mRNA expression analysis identified several miRNA-mRNA interactions in the TM cells, highlighting several miRNA master regulators, such as miR-125a-5p, miR-30a-3p, and miR-1275. Additional master miRNA regulators may be identified if we expand our analysis to include predicted targets with moderate confidence, although this would also potentially increase the number of false-positive findings.…”
Section: Mirna Regulation Of Stretch Responsive Genesmentioning
confidence: 87%
“…miR-15a has been reported to be down-regulated in stress-induced senescent human TM cells (70). miR-93 was found to have increased expression in glaucomatous TM cells and induced apoptosis in these TM cells (71). Since our integrative analysis was restricted to only those experimentally validated miRNA targets, additional master miRNA regulators may be identified if we expanded our analysis to include predicted targets with high or moderate confidence, though this would potentially increase the number of false positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Cheng et al found that compared with normal human trabecular meshwork cells, Nrf2 expression was down-regulated in glaucomatous trabecular meshwork cells, e921514-2 and in both cell types, the overexpression of Nrf2 promoted cell viability and reduced cell apoptosis [44]. Also, in 2016, Wang et al showed that microRNA-93 (miRNA-93) inhibited the cell viability and induced apoptosis of the glaucomatous trabecular meshwork cells via the suppression of Nrf2 [45]. These findings support the role of Nrf2 in protecting trabecular meshwork cells from oxidative stress.…”
Section: Oxidative Stress Glaucoma Trabecular Meshwork Cells and Nrf2mentioning
confidence: 99%